2020
DOI: 10.1021/acs.energyfuels.0c00914
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the Pressure Drop and Cost of a Proton Exchange Membrane Fuel Cell by Flow Field Plate Design

Abstract: The flow field plate is a crucial factor affecting the pressure drop and cost of a proton exchange membrane fuel cell (PEMFC). In order to lower the pressure drop and cost of the PEMFC, a novel design method for the flow field plate structure was proposed. One of the originalities was the fact that intelligent manufacturing technology was applied to the design of the flow field plate, and the other one was the analysis of the pressure drop and cost of the PEMFC through experiments. First, the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In the renewable energy domain, proton exchange membrane (PEM) fuel cells have carved out a niche, poised to reshape our energy future. , As the spotlight turns to sustainable energy, refining the performance and efficiency of PEM fuel cells becomes crucial. , Their versatility, from powering vehicles to driving portable electronics, hinges on their inherent parameters, where electric resistance emerges as a fundamental factor …”
Section: Introductionmentioning
confidence: 99%
“…In the renewable energy domain, proton exchange membrane (PEM) fuel cells have carved out a niche, poised to reshape our energy future. , As the spotlight turns to sustainable energy, refining the performance and efficiency of PEM fuel cells becomes crucial. , Their versatility, from powering vehicles to driving portable electronics, hinges on their inherent parameters, where electric resistance emerges as a fundamental factor …”
Section: Introductionmentioning
confidence: 99%
“…Different flow field structures greatly affect the transport and distribution of reaction gases inside the battery, thus affecting the efficiency and stability of the reaction. Thus, to solve the technical hurdles of PEMFCs, numerous researchers have done a lot of studies to understand the relationship between the structural and the working details within the cells and stacks, and various new structure designs have been proposed and investigated. A calculated fluid dynamics (CFD) model for the typical PEMFC was developed by Chen et al to study the effect of the geometric dimensions of the inlet and outlet of the runner on the characteristics of pressure distribution, and the height of the flow channel was identified as one of the key factors influencing these characteristics. The impact of the hydrogen and oxygen inlet positions on the performance of a typical PEMFC was evaluated by the CFD model .…”
Section: Introductionmentioning
confidence: 99%
“…A combination of experiments and numerical simulations was employed to evaluate a 120 mm × 253 mm PEMFC with a channel-type distribution zone by Shimpalee et al 50 They found that the airflow and cooling direction are critical dependent variables affecting the overall performance and local distribution. Liu et al 54 proposed a novel design for channel-type BP. One of the novelties of their study is the application of intelligent manufacturing technology, and the other is the experimental analysis of the pressure drop and cost of PEMFC.…”
Section: Introductionmentioning
confidence: 99%